Human tuberculosis caused by Mycobacterium bovis: a retrospective comparison with Mycobacterium tuberculosis in a Mexican tertiary care centre, 2000–2015 - Pedro Torres-Gonzalez; Miguel E. Cervera-Hernandez; Areli Martinez-Gamboa; Lourdes Garcia-Garcia; Luis P. Cruz-Hervert; Miriam Bobadilla-del Valle; Alfredo Ponce-de Leon; Jose Sifuentes-Osornio (BMC Infectious Diseases, 2016)
Abstract Background Human tuberculosis caused by Mycobacterium bovis is believed to be frequent in developing countries. Transmission is usually through ingestion of unpasteurized dairy products, although airborne contagion is possible. Disease caused by M. tuberculosis or M. bovis is clinically indistinguishable from each other. The aim of this study was to determine the factors associated with M. bovis disease. Methods Retrospective analysis of all culture-positive cases of M. bovis and M. tuberculosis from 2000 to 2015, in a Mexican tertiary-care centre. Sociodemographic, clinical, and radiographic data from medical records were compared. Disease site was classified as pulmonary, extrapulmonary, or pulmonary and extrapulmonary, based on cultures. Results We evaluated 533 cases, 372 (69.7 %) of which were caused by M. tuberculosis and 161 (30.2 %) by M. bovis. Characteristics associated with M. bovis disease were: younger age (aOR 0.97, 95 % CI 0.95–0.98), glucocorticoid use (aOR 2.27, 95 % CI 1.42–3.63), and extrapulmonary disease (aOR 1.80, 95 % CI 1.21–2.69). M. tuberculosis was associated with lower socioeconomic status (aOR 0.52, 95 % CI 0.28–0.97). When we analysed only pulmonary cases, younger age (aOR 0.97, 95 % CI 0.96–0.99), glucocorticoid use (aOR 2.41, 95 % CI 1.30–4.46), and smoking (aOR 1.94, CI 95 % 1.15–3.27) were associated with M. bovis. Both groups showed similar proportions of direct microscopy smear results (respiratory samples) and chest X-ray cavitations. Conclusions Younger age, glucocorticoid use, and extrapulmonary disease were associated with M. bovis as the causative agent of tuberculosis in a group of patients from a tertiary care centre in a country where bovine tuberculosis is endemic. Further studies must be conducted in the general population to determine pathogen-specific associated factors and outcomes.